The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/cells12232675
|View full text |Cite
|
Sign up to set email alerts
|

Inward Operation of Sodium-Bicarbonate Cotransporter 1 Promotes Astrocytic Na+ Loading and Loss of ATP in Mouse Neocortex during Brief Chemical Ischemia

Katharina Everaerts,
Pawan Thapaliya,
Nils Pape
et al.

Abstract: Ischemic conditions cause an increase in the sodium concentration of astrocytes, driving the breakdown of ionic homeostasis and exacerbating cellular damage. Astrocytes express high levels of the electrogenic sodium-bicarbonate cotransporter1 (NBCe1), which couples intracellular Na+ homeostasis to regulation of pH and operates close to its reversal potential under physiological conditions. Here, we analyzed its mode of operation during transient energy deprivation via imaging astrocytic pH, Na+, and ATP in org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…While Hvcn1 (encoding Hv1) gene expression in MG3 subpopulation is relatively low compared to other microglia/macrophages (MG1, 2, 4, and 5; 2.13-fold decrease, p < 0.0001), we found a small but significant elevation of Hvcn1 gene expression in the MG3 of cKO brains post-stroke (1.32-fold increase, p < 0.01; Additional file 1 : Figure S7), which shall alkalinize pH i . Other potential pH i regulating mechanism includes the Na + /HCO3 − cotransporter (NBCe1), which facilitates HCO3 − outward transport (coupled with Na + efflux) to buffer extracellular H + loads in response to neuronal activity [ 64 ], or stimulates inwardly directed HCO3 − transport (coupled with Na + influx) in ischemic stroke conditions [ 65 ]. We detected similarly low levels of Slc4a4 (encoding NBCe1) gene expression in MG3 compared to other microglia/macrophage subpopulations, but stroke triggered a small but significant increase of Slc4a4 gene expression in the MG3 of cKO brains (1.36-fold increase, p < 0.01; Additional file 1 : Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…While Hvcn1 (encoding Hv1) gene expression in MG3 subpopulation is relatively low compared to other microglia/macrophages (MG1, 2, 4, and 5; 2.13-fold decrease, p < 0.0001), we found a small but significant elevation of Hvcn1 gene expression in the MG3 of cKO brains post-stroke (1.32-fold increase, p < 0.01; Additional file 1 : Figure S7), which shall alkalinize pH i . Other potential pH i regulating mechanism includes the Na + /HCO3 − cotransporter (NBCe1), which facilitates HCO3 − outward transport (coupled with Na + efflux) to buffer extracellular H + loads in response to neuronal activity [ 64 ], or stimulates inwardly directed HCO3 − transport (coupled with Na + influx) in ischemic stroke conditions [ 65 ]. We detected similarly low levels of Slc4a4 (encoding NBCe1) gene expression in MG3 compared to other microglia/macrophage subpopulations, but stroke triggered a small but significant increase of Slc4a4 gene expression in the MG3 of cKO brains (1.36-fold increase, p < 0.01; Additional file 1 : Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal activity and local increase of [K + ] O causes astrocyte membrane depolarization during OGD, which activates astrocytic sodium-bicarbonate cotransporters (NBCs) ( Köhler et al, 2018 ). Their activation then increases intracellular Na + and simultaneously reduces the level of intracellular ATP in astrocytes ( Everaerts et al, 2023 ), and therefore contributes to their swelling ( Florence et al, 2012 ; Larsen and MacAulay, 2017 ). Interestingly, based on previous research Walch and Fiacco suggested in their review that the NBCs-dependent swelling occurs after approximately 10 min of the exposure to pathological conditions, and the first 10 min are NBCs-independent ( Walch and Fiacco, 2022 ).…”
Section: Discussionmentioning
confidence: 99%